The Role of Small and Medium Micro Enterprises (MSMEs) In Economic Development in Bandar Lampung - Suci Hayati; Husnul Fatarib (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Micro, small and medium enterprises occupy a strategic position to accelerate structural changes in order to improve the standard of living of many people and are a place for joint business activities for producers and consumers. The Indonesian economy will have a strong foundation if MSMEs become the main productive and competitive actors in the national economy. The importance of the role of MSMEs, the purpose of this study is to determine the role of MSMEs and the problems faced by MSME business actors in economic development. This type of research is a case study research with a qualitative approach. Respondents in this study were SMEs in Bandar Lampung. Sources of data obtained through primary data sources and secondary data with data collection techniques using interviews, observations and documents. The data analysis technique uses research data processing by listening, selecting data, analyzing data, analyzing data and concluding results. The results of this study are that the role of MSMEs is expected to be able to expand the provision of employment opportunities, make a significant contribution to economic growth, and evenly increase incomes as well as increase the competitiveness and resilience of the national economy. The problems faced by MSMEs include declining sales/demand, difficulty and high cost of raw materials, hampered operational distribution, capitalization, and hampered production. Suggestions in this study are that micro and small businesses are expected to be able to adapt to current technology in increasing product competitiveness and optimizing the potential of financial institutions that can be an alternative source of funds for rural MSMEs.